2017
DOI: 10.1093/aje/kwx291
|View full text |Cite
|
Sign up to set email alerts
|

Association of DNA Methylation-Based Biological Age With Health Risk Factors and Overall and Cause-Specific Mortality

Abstract: Measures of biological age based on blood DNA methylation, referred to as age acceleration (AA), have been developed. We examined whether AA was associated with health risk factors and overall and cause-specific mortality. At baseline (1990-1994), blood samples were drawn from 2,818 participants in the Melbourne Collaborative Cohort Study (Melbourne, Victoria, Australia). DNA methylation was determined using the Infinium HumanMethylation450 BeadChip array (Illumina Inc., San Diego, California). Mixed-effects m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
124
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 121 publications
(142 citation statements)
references
References 54 publications
13
124
2
3
Order By: Relevance
“…As in previous studies, we observed consistently stronger associations with both cancer risk and survival for measures derived from the Hannum predictor, which was validated using blood samples. Therefore, although measures derived from the Horvath predictor may be more generalizable because they have been validated across multiple tissue types, our findings indicate that a predictor validated on the tissue on which it is used might be preferable.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…As in previous studies, we observed consistently stronger associations with both cancer risk and survival for measures derived from the Hannum predictor, which was validated using blood samples. Therefore, although measures derived from the Horvath predictor may be more generalizable because they have been validated across multiple tissue types, our findings indicate that a predictor validated on the tissue on which it is used might be preferable.…”
Section: Discussionsupporting
confidence: 88%
“…While several studies have assessed the association of age acceleration with mortality, there have been fewer analyses of cancer incidence and cancer survival. Levine et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Identification of the critical elements responsible for the loss of epigenetic surveillance is important for understanding the impact of CpG mutations, polymorphisms, and changes in their surrounding sequences and for designing appropriate diagnostic tools. A better understanding of the mechanisms underlying these processes will also help us identify the environmental factors that play a regulatory role in formulating our epigenome [11,47,48] and their effects on epigenetic heredity [49]. Moreover, it improves our understanding of the splicing and alternative splicing processes, which are still poorly understood [5052].…”
Section: Discussionmentioning
confidence: 99%